2007
DOI: 10.1016/j.fusengdes.2007.07.027
|View full text |Cite
|
Sign up to set email alerts
|

MoS2 coatings for the narrow support elements of the W-7X nonplanar coils

Abstract: WENDELSTEIN 7-X (W7-X) is a stellarator presently under construction and assembly in Greifswald, Germany. The superconducting magnet system of W7-X consists of planar and non planar coils. The electromagnetic forces on the superconducting magnet are supported by backing of all coils against a central ring and by wedging among coil casings through "Narrow Support Elements" (NSE) that have to satisfy very specific requirements. Anti friction MoS 2 coatings have been developed and tested at room and cryogenic tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 7 publications
1
25
0
Order By: Relevance
“…As an example, Figure 5 shows a friction plot for a PVD-MoS 2 coating in high vacuum. The coating is similar to the one used in the Wendelstein 7-X fusion experiment [5]. The peaks to negative direction are caused by test stops and restarts.…”
Section: Vacuum Environmentmentioning
confidence: 99%
See 3 more Smart Citations
“…As an example, Figure 5 shows a friction plot for a PVD-MoS 2 coating in high vacuum. The coating is similar to the one used in the Wendelstein 7-X fusion experiment [5]. The peaks to negative direction are caused by test stops and restarts.…”
Section: Vacuum Environmentmentioning
confidence: 99%
“…Because frictional heat and mechanical shocks are able to initiate a normal conducting zone, a lubricant must be employed that guarantees low friction sliding without stick-slip at these stick-slip at these supports. Tests have shown that only MoS2 coatings without any additions are able to meet such requirements [5].…”
Section: Introduction-lubricating Properties Of Mosmentioning
confidence: 99%
See 2 more Smart Citations
“…The main part of a NSE is an aluminium bronze pad, PVD coated on its spherical surface with MoS 2 [3]. During energization of the magnet system it slides against the opposite plane stainless-steel coil housing which is sprayed with MoS 2 .…”
Section: Introductionmentioning
confidence: 99%